Behavior and Limit States of Long-Span Composite Floor Beams with Simple Shear Connections subject to Compartment Fires: Experimental Evaluation - Choe, Lisa; Ramesh, Selvarajah; Grosshandler, William; Hoehler, Matthew; Seif, Mina; Gross, John; Bundy, Matthew (Journal of structural engineering (New York, N.Y.), 2020)
This paper presents the results of compartment fire experiments on four 12.8 m long composite floor beams with various end support conditions. Specimens were constructed as partially-composite beams, consisting of W18×35 steel beams and 83 mm thick lightweight concrete slabs cast on top of 76 mm deep ribbed steel deck units. Test variables included two types of simple shear connections (shear-tab and welded-bolted double-angle connections) and the presence or absence of slab continuity over the girders. Each specimen was subjected to gravity loading using hydraulic actuators and 4000 kW compartment fires produced using natural gas-fueled burners. This study evaluated the characteristics of the fire loading and thermal and structural responses of the specimens. The test results indicated that there were significant effects of thermal restraints on the behavior and failure modes of the specimens with simple shear connections. The specimens resisted gravity loads at large vertical displacements near midspan (approximately a ratio of span length over 20) without collapse under fire loading. However, various limit states and vulnerabilities to fires were observed, including local buckling of steel beams near supports, flexural failure (yielding of steel beams and concrete fracture near restrained end supports), and connection failure (weld shear or bolt shear) during heating and cooling which could lead to partial or total collapse of the floor system.